The Types of Trigona Bee (Apidae: Meliponinae) in Three Different Habitat in South Sumatra - Ani Suderajat; Riyanto Riyanto; Mulawarman Mulawarman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Bees are known to be useful directly or indirectly in human life and ecosystem. This study aims to obtain information about the types of Trigona bees in three different habitats in South Sumatra. This research uses a descriptive method with a purposive sampling technique. Identification is done by observing the morphological characters. Trigona bee samples were taken from three different habitats, namely the Indralaya Sriwijaya University campus, the village of Aurduri Muara Enim, and the village of Kota Agung Lahat. The research found three species of Trigona bees from three different habitats. The three species are from three subgenera, namely Tetragonula, Heterotrigona, and Lepidotrigona. The location of the habitat for the Indralaya Sriwijaya University campus was found Tetragonula laeviceps, andÃÂ Heterotrigona itama. The habitat of the village of Aurduri Muara Enim was found ÃÂ T. laevicepsÃÂ andÃÂ Lepidotrigona terminate. The location of the habitat for the village of Kota Agung Lahat was found ÃÂ T. laeviceps. The most common type of Trigona bee and found in almost every type of habitat isÃÂ T. laeviceps.ÃÂ H. itamaÃÂ is only found on the Indralaya Sriwijaya university campus, while L. Terminate is only found in the village of Aurduri Muara Enim. Conclusion Trigona bees from 3 different habitats in South Sumatra found as many as 3 subgenuses, namely Tetragonula, Heterotrigona, and Lepidotrigona. The types of Trigona bees areÃÂ T. laeviceps,ÃÂ H.itama, andÃÂ L. terminata.ÃÂ